Preservice mathematics teachers’ ways of using problem solving strategies while solving mathematical word problems - Bulut, Neslihan; Karamık, Gözdegül (Journal of Human Sciences, 2015)
The aim of this study is to investigate the variety of problem solving strategies used by preservice mathematics teachers while solving different mathematical word problems which require representation standards and to identify which strategy is functional for pre-service teachers to apply with middle-school students. The study was a case study and conducted during the 2009 spring semester. For this study, 150 senior class pre-service teachers of elementary mathematics education were chosen from a public university in Turkey by convenient sampling. Data were collected through an open-ended test developed by researchers. The test was consist of ten mathematical word problems selected from the five sub-learning areas. The test was given to the pre-service teachers and they were asked to solve each problem in different ways. It took 60 minutes for preservice teachers to complete the test. Strategies that pre-service teachers used for solving word problems were categorized by using content analyze. Also interviews were conducted with pre-service teachers in order to identify their opinions about the usability of strategies in middle-school classrooms. Findings revealed that participants are lack of using different strategies while solving word problems. In general the participants did not apply more than one strategy and they used traditional solving strategies instead of extreme ones. Findings of this study will be a guiding spirit to teacher educators for the enhancement of preservice teacher education programs.